Novel series of 1,2,4-trioxane derivatives as antimalarial agents - Mithun Rudrapal; Dipak Chetia; Vineeta Singh (Taylor & Francis Group, 2017)
Among three series of 1,2,4-trioxane derivatives, five compounds showed good in vitro antimalarial activity, three compounds of which exhibited better activity against P. falciparum resistant (RKL9) strain than the sensitive (3D7) one. Two best compounds were one from aryl series and the other from heteroaryl series with IC50 values of 1.24 µM and 1.24 µM and 1.06 µM and 1.17 µM, against sensitive and resistant strains, respectively. Further, trioxane derivatives exhibited good binding affinity for the P. falciparum cysteine protease falcipain 2 receptor (PDB id: 3BPF) with well defined drug-like and pharmacokinetic properties based on Lipinski's rule of five with additional physicochemical and ADMET parameters. In view of having antimalarial potential, 1,2,4-trioxane derivative(s) reported herein may be useful as novel antimalarial lead(s) in the discovery and development of future antimalarial drug candidates as P. falciparum falcipain 2 inhibitors against resistant malaria.